SUMMARIZED DIFFUSION-LIKE MODEL OF INFORMATIONAL PROCESS OF THE KNOWLEDGE POTENTIAL PROPAGATION - Bomba, A. Y.; Nazaruk, M. V.; Kunanec, N. E.; Pasichnyk, V. V. (Radio Electronics, Computer Science, Control, 2015)
The task of development of a generalized diffusion-like model of redistribution processes of knowledge potential in the city socio communicative environment considering replenishment knowledge agents have been decided. Object of research is the process of transferring of knowledge potential in the educational environment at city schools level. The subjects of research are the methods and tools for building a generalized diffusion-like model of information dissemination process of knowledge potential. The educational environment of the city have been offered to present as network graph, whose vertices represent people (agents), who study and participate in educational processes. The notion of knowledge potential of agents that presented as a characteristic of the certain set, the sum of knowledge of an individual’s accumulated during the corresponding period of life have been introduced. The original model approach to information processes dissemination of knowledge potential based on physical analogies, namely the phenomenon of diffusion have been offered. The mathematical and diffusion model of processes redistribution of knowledge potential between agents, that are belonging to the one educational social and communication community (clique) and between agents of different clicks within the limits of school educational level of the city was generalized. The influence of libraries on replenishment the knowledge potential of agents within the limits of click shown and the results of numeral experiments have been presented.